Prosthodontic Treatment for Geriatric Patient with Parkinson Disease - Volvina, Maria; Sumarsongko, Taufik; Rikmasari, Rasmi (Indonesian Journal of Prosthodontic, 2021)
Introduction: Elder population with associated physical and neurological disorders requires special care that needs to be attended by dentists. Dentists have a significant role in geriatric oral health. This case report explains clinical strategies in maxillary full denture and root-supported mandibular overdenture of a Parkinson patient. Case report: An 87-year-old female patient with Parkinson’s disease (PD) was referred for replacement of completely edentulous maxilla and partially edentulous mandibula. Multiple short visits in the morning and manual manipulation were needed to overcome muscle discoordination problem. Individual trays, fast setting impression material, thermoplastic impression compound, pressure indicator paste, non-anatomical teeth with monoplane occlusion, and denture adhesive are required to enhance denture stability. Prostheses were fabricated with metal framework to avoid fracture and repeated repair. Discussion: Parkinson’s disease is a progressive neurological disorder characterized by tremors, rigidity, bradykinesia and postural instability. These symptoms are worsened by psychological factor such as anxiety and stress. Poor motoric coordination is the cause for their increased susceptibility to dental caries and periodontal diseases as found in this patient. Oral muscular movement is essential in fabricating denture with sufficient retention, stability, and comfort. Adverse effect of Parkinson’s disease medication is xerostomia, which was also found in this patient. This lack of saliva strongly affects denture retention and increased mucosa sensitivity, which in turn exacerbate symptoms of Parkinson’s disease. Conclusion: Effective dentures will help in restoring function, esthetics, and psychological condition of the patient.